2016
DOI: 10.1587/transcom.2016nei0002
|View full text |Cite
|
Sign up to set email alerts
|

Improving Performance of Heuristic Algorithms by Lebesgue Spectrum Filter

Abstract: SUMMARYThe previous researches on the chaotic CDMA have theoretically derived the chaotic sequences having the minimum asynchronous cross-correlation. To minimize the asynchronous cross-correlation, autocorrelation of each sequence have to be C (τ) ≈ C × r τ , r = −2 + √ 3, dumped oscillation with increase of the lag τ. There are several methods to generate such sequences, using a chaotic map, using the Lebesgue spectrum filter (LSF) and so on. In this paper, such lowest cross-correlation found in the chaotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Indeed, the effectiveness of chaotic time series with negative autocorrelation has been demonstrated in previous studies, for example, on code division multiple access (CDMA) in wireless communications by Kohda and Fujisaki [11] and Hasegawa [12]. It has been theoretically shown that the negative autocorrelation in each chaotic spreading sequence minimizes cross-correlation among those sequences.…”
Section: Introductionmentioning
confidence: 92%
“…Indeed, the effectiveness of chaotic time series with negative autocorrelation has been demonstrated in previous studies, for example, on code division multiple access (CDMA) in wireless communications by Kohda and Fujisaki [11] and Hasegawa [12]. It has been theoretically shown that the negative autocorrelation in each chaotic spreading sequence minimizes cross-correlation among those sequences.…”
Section: Introductionmentioning
confidence: 92%
“…In addition, ref. [19] clarifies that the negative autocorrelation that minimizes cross-correlation accelerates the performance of solution search algorithms for combinatorial optimization problems. An FIR filter to generate the optimal chaotic CDMA sequence was also proposed based on the negative autocorrelation analysis [20].…”
Section: Introductionmentioning
confidence: 97%
“…In the literature, the usefulness of negative autocorrelation in time series has been theoretically analyzed regarding code division multiple access (CDMA) [17][18][19]. To achieve high performance in CDMA, the cross-correlation between the spreading sequences must be small.…”
Section: Introductionmentioning
confidence: 99%